Determinants of COVID-19 Vaccination Behavior in Pregnant Women in the Talang Health Center, Tegal Regency (Universitas Negeri Semarang, 2022)
COVID-19 is a Global Pandemic. One of the efforts to overcome COVID-19 is vaccination. The lowest group of vaccine recipients in Tegal Regency was pregnant women (0.02%). COVID-19 was the biggest cause of maternal mortality in 2021 in Tegal Regency (59.1%). The lowest vaccination coverage wat at Talang Community Health Center (8.3%). The strategy for bringing vaccination sites closer has been carried out through the SERPUNG program, supported by sufficient availability of vaccine doses. However, these efforts have not increased coverage, so there is a possibility that behavioral determinants are the cause of the low vaccination coverage. This study aims to determine the determinants of COVID-19 vaccination behavior in pregnant women at Talang Health Center area. This type of research is an analytic survey using a cross sectional approach. The research sample was 100 pregnant women. The sampling technique is Proportionate Stratified Random Sampling. Bivariate analysis (Somers'd and Lambda test) showed that the variables that had no relationship were knowledge (p=0,176), education level (p=0,532), occupation (p=0,794), parity (p=0,826), ANC visit (p=0,393), information access (p=0,525), supported from community leaders (p=0,574), supported from health workers (p=0.192), while the related variable is family support (p= 0.003). Multivariate analysis was performed on the variables resulting from the bivariate analysis with p0.25. The results show that family support is related to COVID-19 vaccination behavior, with an exp value (2.654) = 14.2, it means that respondents have a tendency to behave well by 14.2 times compared to respondents who do not have family support.